Gasification slag sprayed concrete as well as preparation method and application thereof

The gasified slag shotcrete composition with activated silica ash and saline wastewater additives addresses long setting time and high rebound issues, achieving cost-effective and durable shotcrete with improved workability and strength.

CN119191788APending Publication Date: 2024-12-27CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411318760.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Shotcrete prepared using gasified slag to replace part of the sand and gravel has issues with long initial setting time and high rebound rate, and existing methods to address these problems increase costs or compromise durability and environmental sustainability.

Method used

A gasified slag shotcrete composition comprising activated gasified slag silica ash composite, medium sand, silicate cement, fly ash, crushed stone, water reducer, and accelerator, with specific ratios and additives like saline wastewater to stimulate cementitious material activity, promoting hydration reactions and reducing setting time and rebound.

Benefits of technology

The solution effectively reduces initial setting time and rebound rate while enhancing compressive strength, and recycles waste resources, offering cost-effective and durable shotcrete with good workability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052982520000081
    Figure BDA0005052982520000081
  • Figure BDA0005052982520000082
    Figure BDA0005052982520000082
  • Figure BDA0005052982520000101
    Figure BDA0005052982520000101
Patent Text Reader

Abstract

The invention provides gasified slag sprayed concrete which is prepared from the following components in parts by mass: 320 to 750 parts of activated gasified slag silica fume compound, 150 to 550 parts of medium sand, 300 to 500 parts of Portland cement, 50 to 100 parts of fly ash, 500 to 700 parts of gravel, 10 to 20 parts of water reducing agent, 10 to 25 parts of accelerator and 140 to 200 parts of water, wherein the raw materials of the activated gasification slag silica fume compound comprise gasification slag, silica fume and salt-containing wastewater, the mass ratio of the gasification slag to the silica fume to the salt-containing wastewater is (30-70): (1-3): (1-2), the concentration of chloride ions in the salt-containing wastewater is 4000-4500 mg / L, and the concentration of sulfate radicals in the salt-containing wastewater is 69000-78000 mg / L. According to the gasified slag sprayed concrete provided by the invention, the initial setting time and the rebound rate can be effectively reduced, and meanwhile, the compressive strength can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to gasified slag shotcrete and a preparation method and application thereof. Background Art

[0002] Shotcrete is a kind of concrete product that is made by mixing cement, coarse aggregate, fine aggregate, water, water reducer, accelerator and other raw materials in a certain proportion, and spraying it onto the surface of the work surface through a pipe using a special concrete spraying machine and compressed air as the power. Coarse aggregate and fine aggregate are mainly crushed stone and sand respectively. Shotcrete has the advantages of low cost and easy operation, and is a commonly used concrete for tunnel and mine support operations. However, due to the rapid economic development in recent years, China's infrastructure industry has developed rapidly, consuming a large amount of sand and gravel resources, resulting in a surge in the cost of raw materials and products.

[0003] At present, patent CN112047666B discloses an alkali-activated blast furnace nickel-iron slag shotcrete, but in order to reduce the amount of cement in this method, zeolite powder, setting agent (high temperature treatment), and ASA resin are added, resulting in an increase in the cost of shotcrete, and the aging resistance and durability of concrete are deteriorated. Patent CN103359982B discloses a shotcrete prepared by replacing sand and gravel with iron tailings, and the sand and gravel replacement rate is 20wt%-80wt%, but the iron tailings raw materials are not uniform and unstable in nature. Iron tailings contain more heavy metals, which are prone to chemical reactions in a humid environment and under the action of air, which have an adverse effect on the durability and structure of shotcrete, and there is a potential risk of environmental pollution. Patent CN1138169689A discloses a method for preparing shotcrete using coal gangue, which requires crushing and grading the coal gangue, and then soaking it in water, so as to achieve the effect of increasing the workability of the raw materials, but also increases the cost in the concrete preparation process.

[0004] The entrained-bed gasification technology is a process in which coal powder and a gasifying medium are added to a gasifier at the same time, and react under high temperature conditions to generate synthesis gas or coal gas. During the gasification reaction, the minerals in the coal are in a molten state under high temperature conditions, and a part of them is discharged from the gasifier after quenching to obtain gasified slag. As a general industrial solid waste, gasified slag is mainly disposed of by stacking and landfilling, which not only occupies a large amount of land resources, but also causes waste of solid waste resources and pollution to the environment. At present, gasified slag can be used as building backfill in the field of building materials, realizing resource recycling. However, in the prior art, the use of gasified slag to replace part of the sand and gravel for the preparation of concrete still has problems such as long initial setting time and high rebound rate.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The main purpose of the present invention is to provide a gasified slag shotcrete and a preparation method and application thereof, so as to solve one of the problems of the prior art that the shotcrete prepared by using gasified slag to replace part of the sand and gravel has a long initial setting time and a high rebound rate.

[0007] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided a gasified slag shotcrete, which comprises the following components in parts by weight: 320-750 parts of activated gasified slag silica ash composite, 150-550 parts of medium sand, 300-500 parts of silicate cement, 50-100 parts of fly ash, 500-700 parts of crushed stone, 10-20 parts of water reducer, 10-25 parts of accelerator, and 140-200 parts of water; wherein the raw materials of the activated gasified slag silica ash composite comprise gasified slag, silica ash and saline wastewater, and the mass ratio of the three is (30-70):(1-3):(1-2), the concentration of chloride ions in the saline wastewater is 4000-4500 mg / L, and the concentration of sulfate ions is 69000-78000 mg / L.

[0008] Furthermore, the preparation method of the activated gasified slag-silicon ash composite comprises: uniformly mixing the gasified slag, silicon ash and saline wastewater to obtain the activated gasified slag-silicon ash composite.

[0009] Furthermore, the particle size of the gasified slag is 0.1-0.8 mm.

[0010] Furthermore, the strength grade of silicate cement is not less than 42.5.

[0011] Furthermore, the fly ash is secondary fly ash.

[0012] Furthermore, the fineness of the fly ash is 45 μm, and the sieve residue is not more than 20%.

[0013] Furthermore, the particle size of the silica fume is 0.1 μm-0.3 μm.

[0014] Furthermore, the particle size of the medium sand is 0.25-0.5 mm.

[0015] Furthermore, the particle size of the crushed stone is 6-18 mm, and further, the crushed stone includes at least one of river pebble crushed stone and bluestone crushed stone.

[0016] Furthermore, the water reducer includes at least one of a sulfonate water reducer and a polycarboxylate water reducer; further, the sulfonate water reducer includes at least one of calcium lignin sulfonate, sodium lignin sulfonate, and magnesium lignin sulfonate; and the polycarboxylate water reducer includes at least one of maleic anhydride polyoxyethylene ester sulfonate and acrylate acrylate.

[0017] Furthermore, the accelerator includes at least one of an alkali-free accelerator and a low-alkali accelerator; further, the alkali-free accelerator includes at least one of an aluminate alkali-free accelerator, a phosphate alkali-free accelerator, and a urea-formaldehyde alkali-free accelerator; the low-alkali accelerator includes at least one of an alumina clinker-carbonate system and an alumina clinker-alumite system.

[0018] According to another aspect of the present invention, a method for preparing gasified slag shotcrete is provided, comprising the following steps: step S1, mixing activated gasified slag silica fume composite, medium sand and crushed stone once to obtain a primary mixed slurry; step S2, mixing silicate cement, fly ash, water reducer and water with the primary mixed slurry for a second time to obtain a secondary mixed slurry; step S3, mixing an accelerator with the secondary mixed slurry for a third time to obtain a tertiary mixed slurry; step S4, spraying the tertiary mixed slurry to obtain gasified slag shotcrete.

[0019] Further, the temperature of the first mixing is 30-35°C, and the time of the first mixing is 5-15min;

[0020] and / or, the temperature of the secondary mixing is 20-30° C., and the time of the secondary mixing is 5-10 min;

[0021] and / or, the temperature of the three mixing steps is 25-30° C., and the time of the three mixing steps is 0.01-1 min;

[0022] And / or, the pressure of the shotcrete construction is 0.3-0.8MPa.

[0023] According to a third aspect of the present invention, there is provided an application of the gasified slag shotcrete provided in the first aspect or the gasified slag shotcrete prepared by the preparation method provided in the second aspect in the field of coal chemical building materials.

[0024] By applying the technical solution of the present application, the gasified slag shotcrete provided by the present application adds an activated gasified slag silica ash composite to the raw materials. The activated gasified slag silica ash composite is coordinated with gasified slag, silica ash and saline wastewater in a specific mass ratio, and the sulfate and chloride ions in the saline wastewater are used to stimulate the activity of the cementitious materials in the gasified slag and silica ash, promote the dissolution and reaction of the active SiO2 and Al2O3 in the gasified slag and silica ash, accelerate the hydration reaction process, and thus effectively reduce the initial setting time and rebound rate of the gasified slag shotcrete, while also enhancing the compressive strength.

[0025] In addition, the gasified slag shotcrete provided by the present application replaces part of the natural sand (medium sand) with gasified slag, thereby reducing the cost of the gasified slag shotcrete, realizing the recycling of waste solid and waste liquid resources, and the various components in the gasified slag shotcrete synergize with each other, so that the gasified slag shotcrete also has the characteristics of easy availability of raw materials, good workability and high durability. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0027] As analyzed in the background technology of this application, the shotcrete prepared by replacing sand and gravel with gasified slag in the prior art has problems such as long initial setting time, high rebound rate, poor durability, high raw material cost, and poor workability. In order to solve the above problems, this application provides a gasified slag shotcrete and its preparation method and application.

[0028] In a first typical embodiment of the present application, a gasified slag shotcrete is provided, characterized in that it comprises the following components in parts by mass: 320-750 parts of an activated gasified slag silica ash composite, 150-550 parts of medium sand, 300-500 parts of silicate cement, 50-100 parts of fly ash, 500-700 parts of crushed stone, 10-20 parts of a water reducer, 10-25 parts of an accelerator, and 140-200 parts of water; wherein the activated gasified slag silica ash composite comprises gasified slag, silica ash and saline wastewater, and the mass ratio of the three is (30-70):(1-3):(1-2); the concentration of chloride ions in the saline wastewater is 4000-4500 mg / L, and the concentration of sulfate ions is 69000-78000 mg / L.

[0029] The gasified slag shotcrete provided in the present application has an activated gasified slag and silica ash composite added to the raw materials. The activated gasified slag and silica ash composite is coordinated with gasified slag, silica ash and saline wastewater in a specific mass ratio, and sulfate and chloride ions in the saline wastewater are used to stimulate the activity of cementitious materials in the gasified slag and silica ash, promote the dissolution and reaction of active SiO2 and Al2O3 in the gasified slag and silica ash, accelerate the hydration reaction process, and thus effectively reduce the initial setting time and rebound rate of the gasified slag shotcrete, while also enhancing the compressive strength.

[0030] In addition, the gasified slag shotcrete provided by the present application replaces part of the natural sand (medium sand) with gasified slag, thereby reducing the cost of the gasified slag shotcrete, realizing the recycling of waste solid and waste liquid resources, and the various components in the gasified slag shotcrete synergize with each other, so that the gasified slag shotcrete also has the characteristics of easy availability of raw materials, good workability and high durability.

[0031] Typically but not restrictively, in the gasified slag shotcrete provided in the present application, the amount of activated gasified slag silica fume composite is, by weight, 320 parts, 340 parts, 400 parts, 430 parts, 460 parts, 500 parts, 550 parts, 600 parts, 650 parts, 700 parts, 720 parts, 750 parts or a range consisting of any two values; the amount of medium sand is, for example, 150 parts, 250 parts, 350 parts, 450 parts, 550 parts or a range consisting of any two values; the amount of silicate cement is, for example, 300 parts, 350 parts, 400 parts, 450 parts, 500 parts or a range consisting of any two values; the amount of fly ash is, for example, 50 parts , 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or any two parts of the range; the amount of crushed stone is 500 parts, 550 parts, 600 parts, 650 parts, 700 parts or any two parts of the range; the amount of water reducer is 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts or any two parts of the range; the amount of accelerator is 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 25 parts or any two parts of the range; the amount of water is 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts or any two parts of the range.

[0032] Typically but not limitatively, in the activated gasified slag-silicon ash composite provided in the present application, the masses of gasified slag, silica ash and saline wastewater are, for example, 30:1:1, 30:3:1, 40:1.5:1.2, 50:2:1.4, 60:2.5:1.8, 70:1:1, 70:3:2 or a range consisting of any two values.

[0033] Typically but not limiting, the concentration of chloride ions in the saline wastewater is 4000 mg / L, 4100 mg / L, 4200 mg / L, 4300 mg / L, 4400 mg / L, 4500 mg / L or a range consisting of any two values; the concentration of sulfate in the saline wastewater is 69000 mg / L, 70000 mg / L, 71000 mg / L, 72000 mg / L, 73000 mg / L, 74000 mg / L, 75000 mg / L, 76000 mg / L, 77000 mg / L, 78000 mg / L or a range consisting of any two values.

[0034]

Activated Fumed Slag Silica Fume Composite

[0035] Gasification slag

[0036] Gasified slag raw materials are easily available, low in cost, stable in chemical properties, and have physical properties similar to those of natural sand (medium sand). In addition, its density is lower than that of natural sand (medium sand). Using gasified slag instead of natural sand (medium sand) to prepare shotcrete can effectively reduce the rebound rate of shotcrete.

[0037] The main component of gasification slag is glassy aluminosilicate. The calcium component in the gasification slag forms a eutectic with silicon-aluminum substances after high-temperature reaction and solidifies in the gasification slag. It will not cause lime bursting when used in building materials. After high-temperature reaction in the gasification furnace, the active substances such as dicalcium silicate, tricalcium silicate, and tricalcium aluminate in the gasification slag have hydration and gelling properties and can react chemically with fly ash, cement, etc.

[0038] In addition, the gasified slag produced after being crushed by the slag crusher contains relatively abundant pores and has certain water absorption. When applied to concrete, it effectively increases the workability of mixing the gasified slag with other raw material components of concrete; at the same time, the rough surface of the gasified slag increases the bonding force with cement, thereby promoting the lateral deformation ability of aggregate and increasing the strength of concrete.

[0039] Silica Fume

[0040] The main component of silica fume is silicon dioxide. Its fine particles have a good filling effect and can be evenly filled in the voids of shotcrete. Its low hydrothermal and high pozzolanic properties enhance the early and final strength of shotcrete. Therefore, adding silica fume to shotcrete is beneficial to improving the strength and durability of concrete. In addition, silica fume can also improve the anti-permeability of shotcrete.

[0041] Salty wastewater

[0042] By adding salt-containing wastewater to the gasified slag and silica fume, it is beneficial to stimulate the activity of the cementitious material, promote the dissolution and reaction of active SiO2 and Al2O3 in the gasified slag and silica fume, accelerate the hydration reaction process, and make the prepared gasified slag shotcrete have the characteristics of short initial setting time, low rebound rate and high compressive strength.

[0043] Using saline wastewater as an activator, the higher concentration of SO4 in the wastewater 2- It is beneficial to stimulate the activity of gasified slag and silica fume, increase the dissolution rate of active components such as SiO2 and Al2O3 in gasified slag and silica fume, accelerate the formation of calcium aluminate hydrate gel (ASH) and calcium silicate hydrate gel (CSH), increase the hydration reaction rate, and thus reduce the initial setting time of shotcrete. 2- In Ca 2+Under the action of , it reacts with Al2O3 in the dissolved liquid phase to form hydrated calcium sulfoaluminate, which can expand and fill the pores, thereby improving the strength of shotcrete. In addition, the residual carbon of gasified slag will form a hydrophobic film on the surface of the material after it meets water, which will hinder the further penetration of water and affect the reaction of active oxides SiO2, Al2O3 and hydration product Ca(OH)2. - and Ca 2+ It has a strong diffusion capacity and can pass through the hydration layer on the surface of the material, react with the active Al2O3 inside to form hydrated calcium chloroaluminate, and increase the hydration reaction rate. CaCl2 can also react with Ca(OH)2 to form water-insoluble calcium oxychloride complex salt, increase the solid phase ratio, and improve the compressive strength of shotcrete.

[0044] SO4 in saline wastewater 2- With Cl - Too high or too low concentration is not conducive to the performance of gasified slag shotcrete. SO4 2- With Cl - When the concentration is too low, it is difficult to stimulate the activity of gasified slag and silica fume, which is not conducive to the dissolution of active components such as SiO2 and Al2O3 in gasified slag and silica fume, reducing the hydration reaction rate, thereby increasing the initial setting time and rebound rate of gasified slag shotcrete; SO4 2- With Cl - When the concentration of SO4 is too high, 2- Reacts with calcium in cement hydration products, causing concrete expansion and damage. - It will corrode the steel mesh, thereby accelerating the corrosion of gasified slag shotcrete and reducing the compressive strength of the shotcrete.

[0045] The saline wastewater in this application comes from the high-concentration brine on the crystallization side of the water treatment salt in the chemical plant or the high-concentration brine after evaporation and concentration in the evaporation pond. The salt mass concentration is high, that is, the salinity is significantly higher than that of conventional surface water or ordinary production and living water. It mainly contains SO4 2- , Cl - In the present application, the concentration of chloride ions in the saline wastewater is 4000-4500 mg / L, and the concentration of sulfate ions is 69000-78000 mg / L, which is beneficial to reduce the initial setting time and rebound rate of gasified slag shotcrete, and is beneficial to improve the compressive strength.

[0046] In order to reduce the rebound rate of gasified slag shotcrete and improve workability and compressive strength, the particle size of the gasified slag is preferably 0.1 mm-0.8 mm.

[0047] Typically but not restrictively, in the gasified slag shotcrete provided in the present application, the particle size of the gasified slag is, for example, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm or a range consisting of any two values.

[0048] It should be noted that the gasified slag in the present application is derived from the entrained-bed gasification process of the gasification plant of the Coal-to-Liquids Branch of Ningxia Coal Industry Co., Ltd. of the State Energy Group.

[0049] There is no specific limitation on the silica fume in the present application, and any silica fume commonly used in the art can be used. The silica fume in the present application is common commercially available silica fume. In order to further increase the strength and durability of shotcrete, the particle size of the silica fume is preferably 0.1 μm-0.3 μm.

[0050] In some embodiments, the preparation method of the activated fumed slag-silicon ash composite is: uniformly mixing fumed slag, silicon ash, and saline wastewater to obtain the activated fumed slag-silicon ash composite.

[0051] The mixing method is not particularly limited, and various mixing methods are possible. The mixing temperature is also not particularly limited, and is preferably 20-35°C (such as 20°C, 25°C, 30°C, 35°C, etc.).

[0052]

Mid sand

[0053] Medium sand comes from natural sand. It is the main material of concrete. It is difficult to meet the working properties when used alone in concrete. It needs to be used in combination with other raw materials to make the fineness modulus and particle grading meet the requirements to ensure the workability, strength and other properties of concrete. The particle size of medium sand has a certain influence on the strength of shotcrete and the viscosity during the mixing process. Too large or too small a particle size is not conducive to enhancing the strength of concrete. In order to further enhance the workability and strength of concrete, the particle size of medium sand is preferably 0.25mm-0.5mm.

[0054]

Portland cement

[0055] Portland cement has excellent mechanical properties, high strength, and good frost resistance. The sprayed concrete prepared by using it can resist compression, bending, and bending. In addition, Portland cement has excellent gelling properties. The minerals contained in it can be hydrated in a short time to form a solid petrochemical structure, which can increase the hydration rate of cement, thereby increasing the early strength and shortening the initial setting time. In order to further improve the strength and durability of sprayed concrete, it is preferred that the strength grade of Portland cement is not less than 42.5, and it is further preferred that the Portland cement is ordinary Portland cement (PO).

[0056]

Fly ash

[0057] The addition of fly ash is beneficial to improving the strength and durability of shotcrete. The fly ash fills the gaps between cement, which can improve the particle gradation of cementitious materials and further improve the strength of shotcrete. In addition, the glassy active silicon oxide and aluminum oxide in the fly ash react with the cement hydrolysis product calcium hydroxide to generate hydration products such as hydrated calcium silicate and hydrated aluminum silicate, thereby improving the strength of the cementitious material. However, excessive addition of fly ash will increase the setting time of shotcrete. In order to improve the strength of shotcrete, the fly ash is preferably secondary fly ash, and more preferably the fineness of the fly ash is 45μm, and the sieve residue is not more than 20%; in order to make the fly ash easy to obtain, the fly ash is preferably secondary fly ash from a power plant or a power boiler plant, and the ignition loss is less than 5%. On the other hand, the addition of fly ash in this application is beneficial to reducing costs.

[0058]

gravel

[0059] In shotcrete, medium sand and crushed stone both play a skeleton role, which is used to fill in the gaps in cement. Cement is mixed with sand, stone and other raw materials. After the cement hardens, the sand and stone aggregates are cemented into a solid whole. The rough surface of the crushed stone has good cement bonding performance, and the prepared shotcrete has high strength. When the particle size of the crushed stone increases, its total surface area decreases, and the amount of cement wrapped on the surface is reduced accordingly, which can save cement, but there is also difficulty in stirring and is not conducive to bonding. In order to further save cement, improve the strength of the shotcrete and ensure the workability of stirring, the particle size of the crushed stone is preferably 6-18mm. The crushed stone is a crushed stone commonly used in the art, including but not limited to one or more of river pebble crushed stone and bluestone crushed stone.

[0060]

Water reducing agent

[0061] Adding water reducer in the preparation of shotcrete can reduce the amount of cement without affecting the strength of shotcrete, thereby reducing the cost of shotcrete; or, while maintaining fluidity and cement dosage, it can disperse cement particles, reduce water consumption, and thus improve the compressive strength of shotcrete.

[0062] The water reducer in the present application is not specifically limited, and any commonly used water reducer in the art can be used, including but not limited to any one or more of sulfonate water reducers and polycarboxylate water reducers. Preferably, the sulfonate water reducer includes any one or more of calcium lignin sulfonate, sodium lignin sulfonate, magnesium lignin sulfonate, etc.; preferably, the polycarboxylate water reducer includes any one or more of maleic anhydride polyoxyethylene ester sulfonate and acrylate acrylate, so as to further reduce the water consumption while maintaining the slump of the concrete basically unchanged.

[0063]

Accelerator

[0064] Accelerators in shotcrete accelerate the setting and hardening of shotcrete, which helps reduce the rebound rate, inhibit concrete shedding, and enable the concrete to quickly reach a certain strength and quickly form a supporting layer with a certain bearing capacity to meet the engineering needs of shotcrete.

[0065] There is no specific limitation on the accelerator in the present application. Any commonly used accelerator in the art can be used, including but not limited to any one or more of alkali-free accelerators and low-alkali accelerators. Preferably, the alkali-free accelerator includes any one or more of aluminate alkali-free accelerators, phosphate alkali-free accelerators, and urea-formaldehyde alkali-free accelerators. The low-alkali accelerator includes any one or more of alumina clinker-carbonate system and alumina clinker-alunite system, so as to further accelerate the setting and hardening of shotcrete. Among them, the main raw materials of the alumina clinker-carbonate system low-alkali accelerator include alumina clinker, sodium carbonate and quicklime; the main raw materials of the alumina clinker-alunite system low-alkali accelerator include alumina clinker, alumite and zinc sulfate.

[0066] In a second typical embodiment of the present application, a method for preparing the above-mentioned gasified slag shotcrete is provided, and the preparation method comprises the following steps:

[0067] Step S1, mixing the activated gasified slag silica fume composite, medium sand and crushed stone once to obtain a primary mixed slurry; Step S2, mixing the primary mixed slurry with silicate cement, fly ash, water reducing agent and water for a second time to obtain a secondary mixed slurry; Step S3, mixing the accelerator with the secondary mixed slurry for a third time to obtain a tertiary mixed slurry; Step S4, spraying the tertiary mixed slurry to obtain gasified slag shotcrete.

[0068] In order to make the primary mixed slurry more stable, it is preferably allowed to stand for 1.5-3 hours after the primary mixing, and then the primary mixed slurry is obtained.

[0069] In order to better mix the various raw material components in each step, it is preferred that the temperature of the first mixing is 30-35°C, and the time of the first mixing is 5-15 minutes; the temperature of the second mixing is 20-30°C, and the time of the second mixing is 5-10 minutes; the temperature of the third mixing is 25-30, and the time of the third mixing is 0.01-1 minute.

[0070] In order to further improve the efficiency of shotcrete construction, the preferred shotcrete construction pressure is 0.3-0.8 MPa.

[0071] In a third typical embodiment of the present application, there is provided an application of the gasified slag shotcrete provided in the first typical embodiment or the gasified slag shotcrete prepared by the preparation method provided in the second typical embodiment in the field of coal chemical building materials.

[0072] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0073] Example 1

[0074] The present embodiment provides gasified slag shotcrete, which comprises, by weight, 750 parts of activated gasified slag silica fume composite, 150 parts of medium sand (particle size 0.25mm-0.5mm), 420 parts of Portland cement (PO 42.5), 80 parts of fly ash (fineness 45μm, sieve residue 18%), 600 parts of crushed stone (particle size 6-18mm), 20 parts of sodium lignin sulfonate water reducer, 20 parts of phosphate alkali-free quick setting agent, and 180 parts of water; wherein the activated gasified slag silica fume composite comprises gasified slag (particle size 0.1mm-0.8mm), silica fume (particle size 0.1μm-0.3μm), and saline wastewater, and the mass ratio of the three is 70:3:2.

[0075] The main chemical components and mass fractions in the gasification slag are shown in Table 1. The chloride ion concentration, sulfate ion concentration, ammonia nitrogen concentration, alkalinity, hardness and COD in the saline wastewater are shown in Table 2.

[0076] Table 1

[0077]

[0078] Table 2

[0079]

[0080] Example 2

[0081] The difference between Example 2 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 320 parts and the medium sand is 550 parts in the fumed slag shotcrete provided in Example 2. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 30:1:1.

[0082] Example 3

[0083] The difference between Example 3 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 340 parts and the medium sand is 550 parts in the fumed slag shotcrete provided in Example 3. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 30:3:1.

[0084] Example 4

[0085] The difference between Example 4 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 720 parts and the medium sand is 150 parts in the fumed slag shotcrete provided in Example 4. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 70:1:1.

[0086] Example 5

[0087] The difference between Example 5 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 427 parts and the medium sand is 450 parts in the fumed slag shotcrete provided in Example 5. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 40:1.5:1.2.

[0088] Example 6

[0089] The difference between Example 6 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 534 parts and the medium sand is 350 parts in the fumed slag shotcrete provided in Example 6. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 50:2:1.4.

[0090] Example 7

[0091] The difference between Example 7 and Example 1 is that, by weight, the activated fumed slag silica fume composite is 643 parts and the medium sand is 250 parts in the fumed slag shotcrete provided in Example 7. The mass ratio of fumed slag, silica fume and saline wastewater in the activated fumed slag silica fume composite is 60:2.5:1.8.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that in the gasified slag shotcrete of Comparative Example 1, the activated gasified slag silica fume composite is 845 parts, and the medium sand is 50 parts, wherein the mass ratio of gasified slag, silica fume and saline wastewater is 80:4:0.5.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that in the gasified slag shotcrete of Comparative Example 2, the activated gasified slag silica fume composite is 92 parts and the medium sand is 800 parts, wherein the mass ratio of gasified slag, silica fume and saline wastewater is 5:0.2:4.

[0096] Comparative Example 3

[0097] The difference between Comparative Example 3 and Example 1 is that no saline wastewater is added to the activated gasified slag silica fume composite in Comparative Example 3.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 1 is that, by weight, the activated fumed slag silica ash composite provided in Comparative Example 4 contains only fumed slag and saline wastewater, and the mass ratio of fumed slag to saline wastewater is 0.15:1. 2-The concentration of chlorine is 1700 mg / L, and the concentration of Cl- is 900 mg / L. No additional water is added when preparing gasified slag shotcrete.

[0100] Comparative Example 5

[0101] The difference between Comparative Example 5 and Example 1 is that, by weight, the activated fumed slag silica ash composite provided in Comparative Example 5 contains only fumed slag and saline wastewater, and the mass ratio of fumed slag to saline wastewater is 0.3:1. 2- The concentration of chlorine is 1700 mg / L, and the concentration of Cl- is 900 mg / L. No additional water is added when preparing gasified slag shotcrete.

[0102] Comparative Example 6

[0103] The difference between Comparative Example 6 and Example 1 is that, by weight, the gasified slag shotcrete provided in Comparative Example 6 contains 320 parts of silicate cement and 180 parts of fly ash.

[0104] Comparative Example 7

[0105] The difference between Comparative Example 7 and Example 1 is that no silica ash is added to the activated gasified slag silica ash composite of Comparative Example 7, wherein the activated gasified slag silica ash composite is 750 parts by mass, and the mass ratio of gasified slag to saline wastewater in the activated gasified slag silica ash composite is 73:2.

[0106] Comparative Example 8

[0107] The difference between Comparative Example 8 and Example 1 is that, by weight, the SO4 content of the salt-containing wastewater in the activated gasified slag silica ash composite provided in Comparative Example 8 is 2- 150000mg / L, Cl - It is 8000mg / L.

[0108] Test Example 1

[0109] In order to determine the various properties of gasified slag shotcrete, the gasified slag shotcrete samples provided in the embodiments and comparative examples were naturally cured for 28 days after slurry construction, and the slump, initial setting time, rebound rate and 28d compressive strength were tested by demolding. The results are shown in Table 3.

[0110] Test Example 2

[0111] The gasified slag shotcrete samples provided in the embodiment and the comparative example were naturally cured for 100 days after slurry construction, and the samples were demoulded and tested for 100-day compressive strength. The results are shown in Table 3.

[0112] Shotcrete slump test: The slump test is carried out in accordance with the Standard for Test Methods for Performance of Ordinary Concrete Mixtures GB / T50080-2016.

[0113] Initial setting time test: Test in accordance with GB / T 50080-2016 "Concrete Engineering Quality Inspection Standard".

[0114] Rebound rate test: The test is carried out in accordance with GB50086-2015 "Technical Specifications for Geotechnical Anchors and Shotcrete Support Engineering".

[0115] Compressive strength test: The compressive strength test is carried out in accordance with "Test methods for mechanical properties of ordinary concrete" GB / T 50081-2002.

[0116] Table 3

[0117]

[0118]

[0119] According to Examples 1-7 and Comparative Examples 1-2, when the mass ratio of fumed slag, silica ash and saline wastewater in the activated fumed slag silica ash composite is (30-70):(1-3):(1-2), the fumed slag shotcrete has a low slump, a short initial setting time, a low rebound rate and a high 28d compressive strength; when the component ratio in the fumed slag silica ash composite is changed, the slump, initial setting time and rebound rate of the fumed slag shotcrete are significantly increased, and the 28d compressive strength is significantly reduced, indicating that the fumed slag, silica ash and saline wastewater of a specific composition and ratio cooperate with each other, effectively reducing the slump, initial setting time and rebound rate of the fumed slag shotcrete, while also enhancing the compressive strength.

[0120] According to Example 1, Comparative Examples 3-5, and Comparative Example 8, the gasified slag shotcrete prepared in Example 1 has low slump, short initial setting time, low rebound rate, and high 28d compressive strength, while when no saline wastewater is added in Comparative Example 3, the slump, initial setting time, and rebound rate of the gasified slag shotcrete are significantly increased, and the 28d compressive strength is significantly reduced, indicating that the saline wastewater is beneficial to stimulating the activity of the cementitious materials in the gasified slag and silica ash, promoting the dissolution and reaction of the active SiO2 and Al2O3 in the gasified slag and silica ash, accelerating the hydration reaction process, and thereby improving the performance of the gasified slag shotcrete.

[0121] Compared with Example 1, when the SO4 in the saline wastewater is reduced in Comparative Examples 4 and 5, 2- When the concentration of Cl- increases, the slump, initial setting time and rebound rate increase significantly, and the 28d compressive strength decreases significantly, indicating that SO4 2- With Cl - When the concentration is too low, it is difficult to stimulate the activity of gasified slag and silica fume, which is not conducive to improving the performance of gasified slag shotcrete. 2-Compared with the Cl- concentration, although the slump, initial setting time and rebound rate after 28 days of natural curing did not increase compared with Example 1, and the 28-day compressive strength did not decrease significantly, its 100-day compressive strength was significantly lower than that of Example 1, indicating that SO4 2- With Cl - When the concentration is too high, it will accelerate the corrosion of gasified slag shotcrete and reduce the compressive strength of shotcrete.

[0122] According to Example 1 and Comparative Example 7, when silica fume is not added to the activated gasified slag silica fume composite, the initial setting time and the rebound rate increase significantly, indicating that the active components such as SiO2 and Al2O3 in the silica fume can help reduce the initial setting time and the rebound rate of the shotcrete.

[0123] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the activated gasified slag silica ash composite is coordinated with gasified slag, silica ash and saline wastewater in a specific mass ratio, and the sulfate and chloride ions in the saline wastewater are used to stimulate the activity of the cementitious materials in the gasified slag and silica ash, promote the dissolution and reaction of the active SiO2 and Al2O3 in the gasified slag and silica ash, accelerate the hydration reaction process, and thus effectively reduce the initial setting time and rebound rate of the gasified slag shotcrete, while also enhancing the compressive strength.

[0124] In addition, the gasified slag shotcrete provided by the present application replaces part of the natural sand (medium sand) with gasified slag, thereby reducing the cost of the gasified slag shotcrete, realizing the recycling of waste solid and waste liquid resources, and the various components in the gasified slag shotcrete synergize with each other, so that the gasified slag shotcrete also has the characteristics of easy availability of raw materials, good workability and high durability.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A gasified slag shotcrete, characterized in that: The invention comprises the following components by weight: 320-750 parts of activated gasified slag silica fume compound, 150-550 parts of medium sand, 300-500 parts of silicate cement, 50-100 parts of fly ash, 500-700 parts of crushed stone, 10-20 parts of water reducer, 10-25 parts of accelerating setting agent and 140-200 parts of water; The raw materials of the activated gasified slag-silicon ash composite include gasified slag, silicon ash and saline wastewater, and the mass ratio of the three is (30-70):(1-3):(1-2), the concentration of chloride ions in the saline wastewater is 4000-4500 mg / L, and the concentration of sulfate ions is 69000-78000 mg / L.

2. The gasified slag shotcrete according to claim 1, characterized in that: The method for preparing the activated gasified slag-silicon ash composite comprises: uniformly mixing the gasified slag, the silicon ash and the saline wastewater to obtain the activated gasified slag-silicon ash composite.

3. The gasified slag shotcrete according to claim 1, characterized in that: The particle size of the gasified slag is 0.1-0.8 mm; And / or, the strength grade of the silicate cement is not less than 42.

5.

4. The gasified slag shotcrete according to claim 1, characterized in that: The fly ash is secondary fly ash, and / or the fly ash has a fineness of 45 μm and a sieve residue of no more than 20%; And / or, the particle size of the silica fume is 0.1 μm-0.3 μm.

5. The gasified slag shotcrete according to claim 1, characterized in that: The particle size of the medium sand is 0.25-0.5 mm; And / or, the particle size of the crushed stone is 6-18 mm, and the crushed stone includes at least one of river pebble crushed stone and bluestone crushed stone.

6. The gasified slag shotcrete according to claim 1, characterized in that: The water reducer includes at least one of a sulfonate water reducer and a polycarboxylate water reducer; Preferably, the sulfonate water reducer comprises at least one of calcium lignin sulfonate, sodium lignin sulfonate and magnesium lignin sulfonate; Preferably, the polycarboxylate water reducer comprises at least one of maleic anhydride polyoxyethylene ester sulfonate and acrylate acrylate.

7. The gasified slag shotcrete according to claim 1, characterized in that: The accelerating setting agent includes at least one of an alkali-free accelerating setting agent and a low-alkali accelerating setting agent; Preferably, the alkali-free setting agent includes at least one of an aluminate alkali-free setting agent, a phosphate alkali-free setting agent, and a urea-formaldehyde alkali-free setting agent; Preferably, the low-alkali quick-setting agent includes at least one of an alumina clinker-carbonate system and an alumina clinker-alumite system.

8. The method for preparing gasified slag shotcrete according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Step S1, mixing the activated gasified slag silica fume composite, the medium sand and the crushed stone to obtain a primary mixed slurry; Step S2, mixing the silicate cement, the fly ash, the water reducing agent, the water and the primary mixed slurry for a second time to obtain a secondary mixed slurry; Step S3, mixing the quick-setting agent and the secondary mixed slurry three times to obtain a tertiary mixed slurry; Step S4, spraying the three mixed slurries to obtain the gasified slag sprayed concrete.

9. The method for preparing gasified slag shotcrete according to claim 8, characterized in that: The temperature of the first mixing is 30-35°C, and the time of the first mixing is 5-15min; And / or, the temperature of the secondary mixing is 20-30° C., and the time of the secondary mixing is 5-10 min; And / or, the temperature of the three mixing is 25-30°C, and the time of the three mixing is 0.01-1min; And / or, the pressure of the spraying construction is 0.3-0.8MPa.

10. Use of the gasified slag shotcrete according to any one of claims 1 to 7 or the gasified slag shotcrete prepared by the preparation method according to claim 8 or 9 in the field of coal chemical building materials.

Citation Information

Cited By

  • Low-resilience sprayed concrete admixture as well as preparation method and application thereof

    CN120058268A